PENERAPAN MODEL PEMBELAJARAN AUDITORY, INTELLECTUALY, REPETITION (AIR) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IVA SDN 032 KUALU - Lusi Febriyanti; Mahmud Alpusari; Zufriady ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The problem of this research is the lack of students learning outcomes in science, it can be seen from students score, only 15 students (42,85%) who reached the KKM (Standard Minimum Criteria) from the total number of students which is 35 students. While the KKM of the school is 75, it means that there are 20 students (57,14%) who did not reach the KKM. Based on these problems, the researcher need to implement the action research Auditory Learning Model, Intellectualy, Repetition (AIR). In the first cycle of the first meeting, the percentage of teachers activity gained 79,1% in both categories, at the second meeting, the percentage increased to 83,3% in both categories. At the first meeting of the second cycle the percentage increased to 87,5% with very good category, at the second meeting of the percentage increased to 91,6% with very good category. Activities of students has increased, in the first cycle of the first meeting the percentage of the student activity gained 66,7% in average categories, at the second meeting of the percentage increased to 83.3% in both categories. At the first meeting of the second cycle the percentage increased to 87.5% with very good category, and at the second meeting of the percentage increased to 91.6% with very good category. The Average students achievement before the application is 69,28 and increased to 78,28 in the first cycle, and increase again to 85,57 in the second cycle. While the classical completeness in the second cycle is reached. This means that the Auditory, Intellectualy, Repetition (AIR) implementation can increase students achievement in science in fourth grades of SDN 032 Kualu.Key Words: Model Auditory Intellectualy Repetition (AIR), Science achievement